Efficiency performance of Malaysian brackish water white shrimp production - Lim, Ghee Thean (2014)
Shrimp aquaculture industry is playing a vital role in Malaysia agricultural economy, especially its increasing contribution to balance of trade of agricultural products. Brackish water white shrimp production is the main contributor of Malaysian shrimp aquaculture industry. However, Malaysian brackish water white shrimp production is facing low productivity performance and issue of environmental degradation that caused by shrimp culturing. Hence, this study attempts to measure technical, allocative and cost efficiency, and production risk of Malaysian brackish water white shrimp production. Parametric (stochastic frontier analysis) and non parametric approaches (data envelopment analysis) are applied in this study. In this study, dependent variables are production of white shrimp and cost of production; while independent variables are quantity of inputs (labour, feed and seed) and price of inputs (labour, feed and seed). In addition, the factors such as full-time, farmer‟s age, education level, experience, seminar, land ownership, pond size, number of ponds, pond age, fertilization, size of fry and culturing days are applied in technical inefficiency and cost inefficiency analyses. Average scores of technical, allocative and cost efficiency that generated by parametric approach are 54.7%, 66.3% and 36.4%, respectively. While average scores of technical, allocative and cost efficiency that generated by non parametric approach are 43.3%, 59.9% and 26.1%, respectively. Besides, result of production risk analysis indicated that labour is considered as a risk decreasing input, but feed and seed are considered as risk increasing inputs. Results of parametric and non parametric approaches consistently showed that factor of seminar negatively and significantly affect technical inefficiency and cost inefficiency. Hence, government authority should organize more seminars that related to shrimp aquaculture, management, accounting and motivation for the shrimp farmers. Besides, government authority should implement mandatory attendance at seminar for the shrimp farmers. Efficiency performance of Malaysian brackish water white shrimp production needs to be improved in order to achieve higher productivity, at the same time minimize the environmental degradation.